Association between albumin and C‐reactive protein and ankle‐brachial index in haemodialysis. (8th October 2018) - Tsai, Hui‐Ju; Huang, Jiun‐Chi; Tsai, Yi‐Chun; Chen, Ling‐I; Chen, Szu‐Chia; Chang, Jer‐Ming; Chen, Hung‐Chun
ABSTRACT: Aim: Peripheral artery occlusive disease (PAOD) is associated with increased rates of cardiovascular mortality, morbidity and hospitalization in patients undergoing dialysis. An ankle‐brachial index (ABI) less than 0.9 has been used to diagnose PAOD. The aim of this study was to evaluate associations among inflammation, malnutrition and their interactions on the risk of PAOD. Methods: Two hundred and twenty‐two haemodialysis patients (mean age 61.0 ± 11.7 years, 56.8% men) were enrolled and stratified into four groups according to median values of albumin (3.87 g/dL) and logarithm of C‐reactive protein (CRP) (0.48 mg/L). Associations between the study groups and an ABI less than 0.9 were assessed using multiple logistic regression analysis. Receiver operating characteristic curves were constructed to predict an ABI less than 0.9. Results: A lower level of albumin and higher level of CRP were significantly associated with an ABI less than 0.9 in multivariate analysis (odds ratio, 5.688; 95% confidence interval, 1.369–23.626; P = 0.017) after adjusting for demographic, clinical, biochemical and medication data. The interaction between albumin and CRP in relation to an ABI less than 0.9 was significant in multivariate analysis (odds ratio, 1.797; 95% confidence interval, 1.258–2.568; P = 0.001). The areas under the curve for albumin, CRP and albumin + CRP for the prediction of ABI less than 0.9 were 0.311, 0.654 and 0.733, respectively. Conclusion: Patients undergoing haemodialysis with a lower albumin level and higher CRP level have an increased risk of PAOD. A combination of malnutrition and inflammation may be associated with PAOD in haemodialysis patients. Summary at a Glance: This article highlights the associations between peripheral arterial occlusive disease and the combination of malnutrition and inflammation, and their interactions in haemodialysis patients.